(untitled) (LACCEI, 2024)
There are immeasurable small and medium-sized enterprises distributed all over the world that in some cases have certain occupational and financial limits. In turn, they contribute significantly to the economy of each country. Among the main sectors that make up these so-called SMEs are metal-mechanical manufacturing. One of the main problems faced by these manufactures is the production of defective parts in their production lines, which has a great impact on the monthly or annual turnover. For this reason, this research tries to propose an innovative solution to attack the aforementioned problem. This, using various analyses related to the lean philosophy and its tools to help counteract this dilemma. This study seeks to implement tools such as 5S, Poka-Yoke, Andon and TPM, in order to reduce defective production in the hinge line of a Peruvian metalworking SME. Through the research, a result of progress was obtained from 29.83% to 13.24% in its defective production indicator, which is reflected in a margin of improvement of 16 percentage points.